Ritueller Erfahrungsraum: Gottesdienst als praktisch-theologischer Ort von Leben und Glauben - Odenthal, Andreas (Questions liturgiques, 2020)
Theology is about experiences people have had with God and with their faith in God. They are ambivalent: on the one hand, there is the experience of God's presence and the presence of the crucified and risen Christ, which on the other hand does not exclude his permanent otherness, otherworldliness and also absence. These experiences are passed on in the space of the church, i.e. they are always condensed, told and celebrated in a new way. They are interpreted by theology. The ecclesiastical communication community is able to expose these coagulated experiences again and again, so that people can connect them with their own basic experiences such as life and death. The role of the church in this is to mediate. Such mediation (mediality) takes place, among other things, in ritual, which at the same time represents the condensed experiences. It stands in the tension between what was found and what was invented: The church's liturgy has grown, it already exists - in this sense it is found. But it must and can always be applied anew to one’s own life - in this sense it is invented. The liturgy "symbolises": Life and faith are "brought together" and find a ritual expression. In this way the liturgy is a space of experience and a source of theological knowledge: as found, it thematises the history of God's salvation with humankind in the many congealed experiences; as continually reinvented, it becomes an expression of the reality of human life before the horizon of salvation history. The liturgy changes the Christian tradition by continuing it. It also changes people by opening the Christian tradition as a horizon for them. And last but not least, it changes theology itself by representing a separate space of experience of the absent God.